2019
DOI: 10.1002/cphc.201801033
|View full text |Cite
|
Sign up to set email alerts
|

First‐Principles Study of Aziridinium Lead Iodide Perovskite for Photovoltaics

Abstract: The long-term stability remains one of the main challenges for the commercialization of the rapidly developing hybrid organicinorganic perovskite solar cells. Herein, we investigate the electronic and optical properties of the recently reported hybrid halide perovskite (CH 2 ) 2 NH 2 PbI 3 (AZPbI 3 ), which exhibits a much better stability than the popular halide perovskites CH 3 NH 3 PbI 3 and HC(NH 2 ) 2 PbI 3 , by using density functional theory (DFT). We find that AZPbI 3 possesses a band gap of 1.31 eV, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…It was found that the CBM state is mainly derived from the contribution of Pb atoms, and the VBM state mainly comes from the contribution of I atoms. This is consistent with the results of most theoretical calculations. ,, These results indicate that the electrons of the CBM and the holes of the VBM are spatially separated. The less overlap of the electron density of the CBM and the hole density of the VBM in space leads to lower carrier recombination rates in monoamino 2D perovskite and diamino 3D perovskite, which is beneficial for obtaining low-loss photovoltaic devices.…”
Section: Resultssupporting
confidence: 92%
“…It was found that the CBM state is mainly derived from the contribution of Pb atoms, and the VBM state mainly comes from the contribution of I atoms. This is consistent with the results of most theoretical calculations. ,, These results indicate that the electrons of the CBM and the holes of the VBM are spatially separated. The less overlap of the electron density of the CBM and the hole density of the VBM in space leads to lower carrier recombination rates in monoamino 2D perovskite and diamino 3D perovskite, which is beneficial for obtaining low-loss photovoltaic devices.…”
Section: Resultssupporting
confidence: 92%
“…This indicates an increase in the number of electron-trapping defects and a decrease in the number of hole-trapping defects with an increasing KI concentration, as illustrated in Figure e. It has been demonstrated that K + ions, as interstitial impurities, could introduce hole-trapping states, while the I-rich environment generally generates abundant electron-trapping levels. Therefore, the substantial increase in the number of electron-trapping states indicates the dominant role of I – ions in altering and regulating the species and concentration of defects in OIHP. However, the role of I – ions has generally been ignored previously, and only the doping of alkali metal ions is considered the key factor in improving the performance of OIHP solar cells. , …”
mentioning
confidence: 88%
“…Previously, the aziridinium cation was predicted to be suitable for the formation of the 3D framework of lead-halide 19,20 and tin-halide 21 perovskites by theoretical calculations. Notably, aziridine itself is a very reactive species that is prone to ring-opening reactions, 22 and encapsulation inside the perovskite framework appeared to be an efficient way to stabilize the unsubstituted aziridinium cation.…”
Section: Introductionmentioning
confidence: 99%